Mexico : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2001)
The Mexican economy has performed well since the last Article IV Consultation. Executive Directors commended the authorities for maintaining prudent fiscal and monetary policies in the face of financial turbulence in emerging markets and the slowdown in the United States. They appreciated the improved fiscal transparency and the robust banking system, and stressed the need to maintain macroeconomic stability. They appreciated the adequate international reserves, and agreed that the country's data are of good quality and adequate to conduct surveillance effectively.